2022
DOI: 10.3389/fendo.2021.774608
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of T Cell Receptor Signaling Pathway Components in Gestational Diabetes Mellitus Patients: Joint Analysis of mRNA and circRNA Expression Profiles

Abstract: ObjectiveGestational diabetes mellitus (GDM) is one of the most common complications of pregnancy, and its pathogenesis is still unclear. Studies have shown that circular RNAs (circRNAs) can regulate blood glucose levels by targeting mRNAs, but the role of circRNAs in GDM is still unknown. Therefore, a joint microarray analysis of circRNAs and their target mRNAs in GDM patients and healthy pregnant women was carried out.MethodsIn this study, microarray analyses of mRNA and circRNA in 6 GDM patients and 6 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Inflammatory cytokines involved in the TNF signalling pathway regulate the insulin signalling pathway through serine phosphorylation to improve T2DM [71]. In addition, T cell receptor signaling pathway may as a pathological mechanism for GDM[72], T2DM phenotype of GK rats may be closely related T cell receptor signaling pathway[73]. The studies reveal that NF-kappa B signaling pathway is a factor involved in the pathobiology of T2DM[74].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines involved in the TNF signalling pathway regulate the insulin signalling pathway through serine phosphorylation to improve T2DM [71]. In addition, T cell receptor signaling pathway may as a pathological mechanism for GDM[72], T2DM phenotype of GK rats may be closely related T cell receptor signaling pathway[73]. The studies reveal that NF-kappa B signaling pathway is a factor involved in the pathobiology of T2DM[74].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that key mediators such as IL-6 and TNF-α produced by periapical in ammation impede insulin receptor signaling in skeletal muscle and liver. 35 These cytokines promoting serine phosphorylation to mediate heterologous inhibition of IRS-1 signaling, which, in turn, counterregulates the insulin response. 36 In accordance, recent molecular evidence related to periapical lesions and immunoin ammatory response offer new therapeutic guidance for endodontic treatment in DM subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Successful and healthy pregnancy outcome depends upon mother's health, her nutrition, hormonal change, optimal adaption in mother, and signaling system, however, GDM disturbs the signaling pathways [76,77]. GDM-associated proteins in the signaling pathways are necessary to understand how GDM develops and progresses as most GDM associated variations have an impact on protein functions.…”
Section: Discussionmentioning
confidence: 99%